A multi‐objective multi‐agent deep reinforcement learning approach to residential appliance scheduling. Issue 4 (12th May 2022) - Lu, Junlin; Mannion, Patrick; Mason, Karl
Abstract: Residential buildings are large consumers of energy. They contribute significantly to the demand placed on the grid, particularly during hours of peak demand. Demand‐side management is crucial to reducing this demand placed on the grid and increasing renewable utilisation. This research study presents a multi‐objective tunable deep reinforcement learning algorithm for demand‐side management of household appliances. The proposed tunable Deep Q‐Network (DQN) algorithm learns a single policy that accounts for different preferences for multiple objectives present when scheduling appliances. These include electricity cost, peak demand, and punctuality. The tunable Deep Q‐Network algorithm is compared to two rule‐based approaches for appliance scheduling. When comparing the 1‐month simulation results for the tunable DQN with an electricity cost rule‐based benchmark method, the tunable DQN agent provides a statistically significant improvement of 30%, 18.2%, and 37.3% for the cost, peak power, and punctuality objectives. Moreover, the tunable Deep Q‐Network can produce a range of appliance scheduling policies for different objective preferences without requiring any computationally intensive retraining. This is the key advantage of the proposed tunable Deep Q‐Network algorithm for appliance scheduling.